PERTIMBANGAN HAKIM DALAM PUTUSAN PEMIDANAAN KEPADA PELAKU TINDAK PIDANA TURUT SERTA MELAKUKAN PENGANIAYAAN (Studi Putusan Nomor 506/Pid.B/2007/PN.Trt) - Sokhiatulo Buulolo (Jurnal Panah Hukum, 2023)
The crime of molestation is a criminal act that intentionally causes pain to others, causes injuries to other people's bodies, and harms the health of others. One of the persecution cases examined and tried by the Tarurung District Court is decision number 506/Pid.B/2007/PN.Trt. In that decision, the defendant was sentenced to acquittal for allegedly violating the provisions in Article 170 paragraph (1) of the Criminal Code and Article 351 paragraph (1) of the Criminal Code Juncto Article 55 paragraph (1) 1e of the Criminal Code. This research was conducted using normative legal research with a statutory approach, a case approach, and an analytical approach. Data collection techniques using secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. The data analysis used is qualitative data analysis by describing all secondary data in descriptive form. Based on the findings of the research and discussion, the authors can conclude that what is considered by the judge to give an acquittal to the defendant is the indictment of Article 170 paragraph (1) as a primary indictment that has one element that is not legally and convincingly proven in the evidence process in the trial. The judge stated that the defendant was found guilty of committing the acts as stated in Article 351 paragraph (1) of the Criminal Code and sentenced to imprisonment for 5 (five) months, but the sentence did not need to be served because in the trial process both parties had reconciled and forgave each other in the trial. . Researchers suggest that law enforcers in carrying out their duties in creating justice do not prioritize the existence of separate institutions, because basically the purpose of law is to create order and peace in the midst of society and readers (academics) and moreover to the community so as not to commit acts of judges themselves to To solve problems, it is better to prioritize the family process or legal channels to resolve a case